Higher Education Students’ Disaster Awareness, Preparedness, and Resiliency Preparation - Mary Grace C. Malonecio (Universal Journal of Educational Research)
Natural disaster affects everyone’s lives regardless of position and status in life but its impact can be mitigated by doing necessary preparations. This survey-correlational research design aimed to determine the disaster awareness, preparedness, and resiliency preparation of the 249 randomly selected higher education students from a state university in the province of Aklan. A 3-part researcher-made questionnaire was utilized to gather data about disaster awareness, preparedness, and resiliency preparation. The instruments were subjected to validity and reliability testing. The statistical tools used in data analyses were mean, standard deviation, Analysis of Variance (ANOVA) and Pearson’s r. Inferential test was set at 5% level of significance. The results revealed that the higher education students had high level of disaster awareness. They also had very high level of disaster preparedness, and very high level of disaster resiliency preparation. There is significant variation in the disaster preparedness of the students. There is also significant difference in the disaster resiliency preparation of the students. Moreover, disaster awareness, disaster preparedness, and disaster resiliency preparation are significantly associated.